Health seeking behavior among women diagnosed with breast cancer attending Kisii teaching and referral hospital in Kisii County - David, Roselyne Nyakona; Araka, Glenn Onsomu; Obare, Obwocha Evans; Mong’are, Samuel (International Journal Of Community Medicine And Public Health, 2022)
Background: Most women with breast cancer are diagnosed at an advanced stage of the disease leading to poor treatment outcomes. Therefore, this study aimed at determining the socio-economic and cultural factors that influence health seeking behavior among women diagnosed with breast cancer in Kisii County. Methods: 96 breast cancer women who were attending the Kisii Teaching and Referral hospital in Kisii County were purposively sampled. A descriptive study design was used. Structured and open-ended questionnaires were the data collection tools. Collected data was analyzed using Chi square and correlation analysis through SPSS. Results: 84.4% of the respondents were rural dwellers, 56.3% of the respondents were Protestants while 69.79% of the respondents were married. Majority (53%) of the respondents had attained a secondary level of education, 54.2% were self-employed while 80.2% of the respondents had a monthly income of KShs 10,000. There was no association between breast cancer treatment and an individual’s level of income (χ2=2.773, p=0.597). 2.1% of the respondents agreed that breast cancer is a curse. Witchcraft was not associated with health seeking behaviour (χ2=9.907, p=0.624). 67.7% of the respondents agreed that breast cancer is a killer disease that metastases fast within the body. Conclusions: The respondent’s education, employment status and level of income are the socio-economic factors that determine health seeking behaviour among women diagnosed with breast cancer in Kisii County. Majority of the victims use traditional medicine as a treatment option for breast cancer because it is cheaper than modern cancer therapy.